Mechanical properties of sawdust and chip wood fibre reinforced epoxy composite - Dandi Bachtiar (Universiti Putra Malaysia Press, 2019)
This chapter presents the investigation of the mechanical properties of untreated sawdust and chip wood fibre reinforced epoxy composites. Three different sizes of sawdust and chip wood fibres were used in this study. The tensile testing results showed the performance of various fibre sizes of reinforced composites at the fibre content of 14% by weight. The highest tensile strength of sawdust/epoxy and chip wood/epoxy composites were 28.917 MPa and 21.951 MPa, respectively, both achieved by the medium fibre size (0.12-0.15 mm and 9-10 mm, respectively). Meanwhile the highest moduli of elasticity of sawdust/ epoxy and chip wood/epoxy were 889.988 MPa and 902.331 MPa respectively, both achieved also by the medium fibre size. The structures of the sawdust and chip wood epoxy composite were examined using scanning electron microscopy (SEM) micrographs to determine the distribution of fibres and the behaviour of sawdust epoxy composites and chip wood epoxy composites.